The problems of spatial ordering and taxation of agricultural lands - Malashevskyi, Mykola; Kuzin, Nataliia; Palamar, Alena; Malanchuk, Mariia (Geodesy and Cartography, 2017)
The problem of rationalizing the use of agricultural land is increasingly complicated in Ukraine. Today it has various aspects, the most important of which are technological, economic, organizational and environmental. That is why the level of use of land in Ukraine is now so critical that further land degradation potential in agriculture can have disastrous consequences.The objective of this paper is to study the economic effects of agricultural land use on example of Kyiv city. It is revealed that the problem of rational use and protection of agricultural land in Ukraine is deteriorating year by year. In today’s conditions, this manifests itself in various directions, among which, in our opinion, the deterioration of the ecological state as a result of irrational use.On examples of land plots of the Kyiv city, the procedure for calculating the normative monetary valuation of agricultural land as one of the main instruments for accompanying capital transactions has been considered. The information on the weak and strong sides of the objects of evaluation is shown, which allows to evaluate the effectiveness of its functioning, current, past and future costs and incomes, as well as development prospects, which as a result serves as the basis for making effective management decisions on the valuation object.According to the research results, which consists in changing the agricultural land purpose in Kyiv city, it was ascertained that the normative monetary valuation of these lands will increase over 6 billion UAH.